The Formation of Landscapes in the Sakhalin and Kuril Islands - Yakou, Hisashi (Actual Problems of Theory and History of Art, 2018)
Sakhalin is one of the most remote areas from the art centers of Russia such as Moscow and St. Petersburg. As such, it has not been an object of close study in regard to the history of art and landscape painting. Except for the northern part of Sakhalin Island, this region was ruled by Japan until the end of World War II, and thus the art history of Sakhalin in a Russian context began only around that time. At first, Sakhalin was represented with a romantic and exotic vision by new settler artists who arrived from different parts of the USSR. As time passed, the artists, some of whom had been born in Sakhalin, tended to face the reality of the region, keeping step with the stylistic changes in Soviet realist paintings, and they produced works with numerous local motifs, such as the ocean, frozen sea, coastlines, islands, volcanoes, fish, seagulls, and sea lions, as well as art featuring the lives of northern indigenous people. At the same time, the crucial role played by the “Shikotan Group” should be stressed if we consider the importance of its activities in the development of typical landscapes of the Kuril Islands. In this paper the focus will be on the analysis of the works by local artists who have been active since the demise of the Soviet Union. Natalia Kiryukhina, a leading artist of Sakhalin, does not conceal her attachment to her homeland, epitomizing its landscapes and sometimes resorting to Russian folklore and artistic crafts. Sergey Vasenkin adores and assiduously learns from Ivan Aivazovsky and seems to transform the individual scenery of Sakhalin into one of ideal, collective Russian landscapes. Looking closely at the works of these artists and others, we can argue that, through the process of representing a place such as Sakhalin, which was the land of indigenous people where the settlers were displaced one by the other, the landscape of the place transfigures itself according to the gaze of viewers and aspires to be an integral part of a broader national structure while retaining its local features.
Keywords: Sakhalin; Kuril Islands; Shikotan Group; landscape painting; Soviet Impressionism; Mediterranean; Crimea; Far East